Communicating with Asia : understanding people and customs. - Irwin, Harry (St. Leonards, N.S.W. : Allen and Unwin, 1996)
The intercultural communication imperative. Understanding intercultural communication. Customs. Identities. Achieving cultural literacy.
Keywords: Culture; Intercultural communication; Intercultural communication; Communication and culture -- Asia; Communication and culture -- Australia; Asia -- Social life and customs; Australia -- Relations -- Asia; Asia -- Relations -- Australia